Capturing the Educational and Economic Impacts of School Closures in Poland - Tomasz Gajderowicz; Maciej Jakubowski; Harry A. Patrinos; Sylwia Wrona (Institute of Labor Economics (IZA), 2022)
The effect of school closures in the spring of 2020 on the math, science, and reading skills of secondary school students in Poland is estimated. The COVID-19-induced school closures lasted 26 weeks in Poland, one of Europe's longest periods of shutdown. Comparison of the learning outcomes with pre- and post-COVID-19 samples shows that the learning loss was equal to more than one year of study. Assuming a 45-year working life of the total affected population, the economic loss in future student earnings may amount to 7.2 percent of Poland's gross domestic product.
Keywords: I21; I24; 330; COVID-19; school closure; learning loss; Poland